EXPLORING GREEN MARKETING PRACTICES: INSIGHTS FROM MARKETING MANAGERS ON ENVIRONMENTAL SUSTAINABILITY - Darekar, Sheetal; Misal, Satyavan; Bagul, Shweta; Banerjee, Sneha; Thakre, Purva (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Creating and promoting items according to their perceived or actual environmental sustainability is referred to as "green marketing." Two instances of green marketing involve highlighting the reduced emissions linked to a product’s manufacturing process or using recycled materials in product packaging. Some companies might further position themselves as mindful businesses by giving a portion of their sales profits to environmental projects like planting trees. Green marketing is part of a broader trend toward socially and environmentally friendly business practices. Consumers are increasingly expecting companies to demonstrate their commitment to improving their operations while also following to various environmental, social, and governance (ESG) standards. To continue to achieve this, a lot of businesses will continue to send out social impact statements in which they transparently track their advancement toward these goals on a regular basis. Reducing the carbon emissions linked to the company’s operations upholding strict labor laws both domestically and in foreign supply chains, and charitable endeavors aimed at benefitting the communities where the company operates are common examples of ESG-related improvements. Green marketing, while primarily referring to environmental measures, is increasingly being offered alongside with corporate governance and social goals. Based on a survey of 120 marketing managers, a collection of green marketing practices is identified in this article.